Cesarean Section Scar Ectopic Pregnancy in the Second Trimester: An Underrecognized Complication of Cesarean Deliveries - Sharonne Holtzman; Mary Louise Kiernan; Jaimie Huntly; Valentin Kolev; Konstatin Zakashansky (Case Reports in Obstetrics and Gynecology)
The aim of this paper is to present a case of a cesarean section ectopic pregnancy (CSP) diagnosed in the second trimester and perform a literature review of current guidelines for the management of CSP in the second trimester. This was exempt from the Mount Sinai IRB. This is a case is of a 35-year-old P1122 at 13w4d who presented to our hospital with vaginal spotting and abdominal pain. The patient was found to have a cesarean section ectopic pregnancy with placenta increta. There are no management guidelines for second trimester CSP, and the published material is minimal. A literature review was completed and demonstrated two cases and one case series published on management of existing literature on management of second trimester CSP. Our patient underwent an uncomplicated total laparoscopic hysterectomy with bilateral salpingectomy, bilateral ureterolysis, and cystoscopy. She had an uncomplicated postoperative course and was discharged on postoperative day three with an unremarkable recovery at her two-week postoperative visit.